Letter - Brown, W.
037-0051-001 ABERDEEN TRADES COUNCIL (Affiliated to the Scottish Trade Union Congress). Secretary: W. BROWN. Council Rooms & Office: 47 Belmont Street, ABERDEEN. 13th September, 1937. Sir Walter Citrine, Transport House, Smith Square, South Block, LONDON. Dear Sir, On 3rd August, 1937 I forwarded to you on behalf of above Council a Money Order to the value of £10 to the appeal on behalf of the Basque Children. As I do not appear to have received a receipt, I shall be glad if you will let me have an acknowledgment at your early convenience. Yours faithfully, W Brown 292/946/37/51